IMPLEMENTASI KEBIJAKAN PENGELOLAAN PAJAK BUMI DAN BANGUNAN DI DINAS PENDAPATAN DAERAH KOTA MANADO - BINGKU, JANWAR; Rumapea, Patar; Ogotan, Martha (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract tax has a role in the execution of development because it is a source of State income tax forall expenditures including expenditures of development. The Earth and building tax is one of the sourcesof income of the area that also determines the conditions of regional financial capability, while intendedto interest the Community area. The lack of socialization about the Earth and building tax payments, in thedetermination of the amount of tax to be paid by the public are often imprecise and understanding of thepeople in the process of tax payment the Earth and buildings that hamper the implementation of the policy, sothat it does not run with the maximum. Based on the issue the purpose of this research was carried out toanalyse the implementation of policy on the management of Tax the Earth and buildings in Manado City areaRevenue Office.This research uses descriptive qualitative approach method. Use this method to answer How theimplementation of Tax management policies of the Earth and buildings in Manado City area Revenue OfficeThe results showed that Governments in the management of the Earth and building Tax (PBB) as payment oftaxes of Earth and building (PBB) has not been fullest seen from the communication to the public is not agood resource as well as in analysing and establishing the potential of Earth andbuilding Tax (PBB) are inadequate and there are still communities that have not followed the procedures canbe viewed from the implementation of management policies building on Earth andthe Tax Office Revenue ManadoKeywords: Tax, policy, Implementation of Earth and building (PBB)